Kepemimpin Kepala Sekolah dan Pembinaan Karier Guru menjadi Bakal Calon Kepala Sekolah - Ade Chandra (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
There are many teachers in school who have a good personality, mastering pedagogic, social mentally, and professional and dedicated. They become the requirement as a school leader, unfortunately, they are a lack of school managerial. So that incompetence to manage school management. The potential teachers should be trained and developed his carrier as the candidate of principal. The carrier training should be directly guided by principal and carrier development through education and training of leadership. These times the training and development teacher carrier for getting the job position certainty in school still un-optimal. The implication of teacher functional position becomes stagnant. It’s not enough they are appreciated by the phrase “teacher, the hero without commendable sign”. It’s a teacher carrier problem that should be found the solution.